Antennas for Ultra-Wideband Applications: Design and Performance Study Using Printed and Dielectric Resonators (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Ultra-wideband (UWB) communication systems may make use of a miniature dielectric resonator antenna. A 50 ohm microstrip line is included into the modified T-shaped feed network to produce strong coupling and some bandwidth augmentation; the antenna element itself is a rectangular low permittivity ceramic block with a dielectric constant of 9.4. Simulations and measurements of the antenna's performance in a range of 3100–5500 MHz reveal an impedance bandwidth of 55.8% and a Voltage Standing Wave Ratio (VSWR) of 2, making it well-suited for ultra-wideband (UWB) uses.